Adolescence as viewed through blogs - CAIROLI, Priscilla (2009)
The use of blogs, as a place for adolescents to write about their experiences, is a growing contemporary phenomenon. The purpose of the present article is to analyze the writing contained in blogs in the make-up of the adolescent subject, from a psychoanalytic perspective. The topic was approached through a review of relevant literature starting with Freud’s legacies about writing, moving on to the work of contemporary psychoanalysts who are researching the subject. Afterwards, issues are presented related to changes experienced in adolescence, as a subjective event, coupled with the writing at that point of time in their life. Finally, some considerations are proposed about writing on the internet and about blogs.